(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Children deal with their fears and their need to attend school in many ways. Some may go through the “morning ritual” but then be unable to leave home or turn back after completing part of the school journey. Others may just refuse to get up, lock themselves in somewhere or run off until it is safe to return home. Some may even endure punishment as the price of not going to school. Many will swear, and mean it at the time, to go this afternoon or tomorrow if they are allowed to stay at home at the present time.As a child, he may have had a few days when he didn’t particularly want to go to school, maybe to avoid a particular classmate or a big homework assignment him failed to complete. This type of reluctance is different from school phobia, a condition wherein a child has a fear of attending school. For these students, walking into a school can be a frightening feeling, and they might be overwhelmed by the school’s size, the number of people in it, or feeling lost. This disorder was given its name in 1941 and may also be known as school refusal.